1986
DOI: 10.1139/v86-267
|View full text |Cite
|
Sign up to set email alerts
|

Squaraine chemistry. On the anomalous mass spectra of bis(4-dimethylaminophenyl)squaraine and its derivatives

Abstract: The electron impact (EI) mass specra of bis(4-dimethylaminopheny1)squaraine 1 and its derivatives 2-14 have been studied. Ions of mass number higher than the molecular ion, which are shown to be precursors of fragment ions of lower mass numbers, are observed. From the structure-property relationship, these ions are assigned to M + CHR1+ and M + Hz1+, where CH2R is the alkyl group in the N,N-dialkylanilino moiety of squaraine. Evidence is provided that the formation of M + CHR1 f and M + Hz1 f. is the result of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 2 publications
1
32
0
Order By: Relevance
“…Regardless of the precursors in these syntheses, the final squaraine formation step involves the condensation of 4 and an N, N-dialkylaniline (9). It becomes obvious that if one can develop an independent synthesis of 4, one would not only be able to op 'mize the reaction condition for the squaraine formation st 1 p, but also have access to unsymmetrical squaraines when an appropriate aniline reactant is chosen.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regardless of the precursors in these syntheses, the final squaraine formation step involves the condensation of 4 and an N, N-dialkylaniline (9). It becomes obvious that if one can develop an independent synthesis of 4, one would not only be able to op 'mize the reaction condition for the squaraine formation st 1 p, but also have access to unsymmetrical squaraines when an appropriate aniline reactant is chosen.…”
Section: Resultsmentioning
confidence: 99%
“…The condition for the condensation reaction is investigated using 4 and N,Ndimethylaniline as reactants. The squaraine product is l a ; the quality of the product obtained can be compared with other l a samples (9). Results showed that, when 4 and N,N-dimethylaniline were condensed in refluxing 1-butanol (2), 1-heptanol (under reduced pressure) (4), or 2-propanol (in the presence of tributyl orthoformate) (1 1, 12), a greenish- solid was obtained.…”
Section: Ch30mentioning
confidence: 99%
See 2 more Smart Citations
“…A number of squaraines were prepared from di-12-butyl squarate using these optimized conditions, and the yields are tabulated in Table 4.12 The yields of the same set of squaraines synthesized by the traditional acid route are also given for comparison (15). Comparison indicates that very similar chemical yields are obtained from both procedures.…”
Section: Scope Of the Ester Route Sjntlzesismentioning
confidence: 99%